Georgia’s foreign trade potential with the United States: A Gravity Model approach - Lang, Irma; Shaburishvili, Shota; Sikharulidze, Davit (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
Shortly after the restoration of Georgia’s independence, the United States became an important strategic partner. On June 20, 2007, a trade and investment framework agreement was signed between the U.S. and Georgia. This agreement is to expand trade in goods and services between countries, as well as to improve the investment environment in Georgia. Although Georgia does not yet have a Free Trade Agreement with the United States, this research aimed to assess the trade potential between Georgia and the U.S. through a gravity model using panel data for the period 2000-2021. The bilateral trade gravity model was evaluated by EGLS, two-stage EGLS, and GMM techniques, which included the following variables: GDP, population, distance, and trade openness between Georgia and partner countries. In addition, dummy variables such as religion, common border, and trade agreement also play a role. The results of the study also revealed that Georgia’s foreign trade potential with the United States is fragile.